Asuhan Kebidanan Continuity of Care pada Ny. D dengan Penerapan Pijat Oksitosin dan Minyak Zaitun - Hida Febrina; Hikmah Ifayanti; Hellen Febrianti (Jurnal Ventilator, 2024)
Continuity of care (COC) or sustainable care is the care provided by a midwife to clients or patients from pregnancy, childbirth, the puerperium, newborn care, and family planning. This study aimed to provide continuity of midwifery care for a primigravida pregnant woman, Mrs. D, at a midwife practice. A case study method was used. The subject was Mrs. D, G1P0A0. Data collection was carried out from September to December 2023. The results showed that during pregnancy Mrs. D complained of sleep difficulties, during childbirth there was bloody show, in the puerperium period milk production was insufficient, the baby had diaper rash, and for family planning she wanted to use the pill. Interventions provided were health education on third trimester discomforts, normal childbirth management with 60 steps of APN, oxytocin massage, and olive oil for the baby. In conclusion, continuity of midwifery care was provided for Mrs. D with oxytocin massage and olive oil interventions. Milk production increased and the baby's diaper rash reduced.